Developing the power of action of individuals and communities, with children and young people - PHILIA Project - Belchior-Rocha, H.; Ferreira, J.; Pena, M.; Álvarez-Pérez, P. (ISWED Online Conference 2021, 2021)
The Philia project goal was to create new training courses, with the collaboration of youngster involved in social services, social workers, researchers, teachers and their students, with the aim to improve the training of social workers for a better efficiency in their practice and we had two strategic themes: networks and success and the objective of strengthen the dynamics, Inclusion, Equality non-discrimination and combating forms of segregation. Research Methods and Techniques Focusing on the importance of formal and informal relations, a collaborative action research was developed in 5 European countries (Germany, Belgium, France, Portugal, Romania), 11 partners and the Toulouse Erasmus training center. In each of the 5 countries, trainers-researchers conducted a survey of young people accompanied by child protection institutions, students in social work and their accompanying professionals. The innovative tools and processes that emerged from the research were tested in practical application by the project stakeholders The development of this power is, for the person being supported and all stakeholders, the possibility to regain freedom and movement.